Frequency of use and functions of the Italian and Spanish interjections used in film language and their impact in dubbing into Spanish - Zamora, Pablo; Alessandro, Arianna (MonTi Monografías de Traducción e Interpretación, 2018)
In a previous publication (Zamora & Alessandro 2013) it was shown that certain single-word, and mostly multi-word interjections are more often used specifically in the Italian linguistic system, and therefore in its film language, than in the Spanish one. In Spanish, other linguistic resources with the same pragmatic and discursive function are used. With the data obtained from our previous investigation and based on a descriptive analysis of an Italian-Spanish film corpus made up by original and dubbed movies, the objectives of this work are, on the one hand, to confirm the frequency of use of specific interjections in both film languages in order to examine the role and the importance of this linguistic resource in the orality of both languages; and, on the other hand, to verify which procedures or patterns have been applied by the translators when dealing with this special class of words.